The role of electrolyte acid concentration in the electrochemical exfoliation of graphite: Mechanism and synthesis of electrochemical graphene oxide - Sean E. Lowe; Ge Shi; Yubai Zhang; Jiadong Qin; Lixue Jiang; Shuaiyu Jiang; Mohammad Al-Mamun; Porun Liu; Yu Lin Zhong; Huijun Zhao (Nano Materials Science, 2019)
Electrochemistry has emerged as a major route for graphene and graphene oxide synthesis from graphite. Anodic graphite oxidation is commonly used with dilute mineral acid or aqueous salt electrolytes. In this system, the electrolyte acid concentration appears to be a critical parameter. However, the effect of the acid concentration, particularly at low concentrations, is still not fully understood. To address this issue, we used a packed bed electrochemical reactor to synthesize seven different electrochemical graphite oxide (EGO) products in 2–16 M sulfuric acid. Detailed XRD, XPS, Raman, conductivity and optical microscopy analysis of the products was carried out. We found dilute acid (<10 M) graphite oxides were less crystalline and less oxidized than those produced in stronger acids. The oxygen evolution reaction at the graphite surface appears to affect the structural changes, oxidation mechanism, and electrochemical corrosion of the anode. EGO conductivity is also strongly affected by the electrolyte’s acidity. We show that well oxidized, yet reasonably conductive, single layer graphene oxide can be produced from 7.1 M acid. These results broaden our understanding of graphite electrochemistry and will serve to inform future electrochemical graphene synthesis efforts. Keywords: Electrochemistry, Graphene, Graphene oxide, Synthesis, Exfoliation